2D surface defect images applying Tikhonov regularized inversion and ECT. (June 2016) - Pasadas, D.J.; Ribeiro, A.L.; Rocha, T.; Ramos, H.G.
Abstract: This paper presents an inversion problem solution to obtain the geometrical profile of defects in a 2D surface view using an eddy current method with sinusoidal excitation. The inversion model deals with the perturbation of the eddy currents when a spatially uniform excitation magnetic field distribution is imposed in the vicinity of a metal surface. An adequate experimental setup was used to measure the magnetic field around a crack region. A planar excitation coil was used to generate the uniform magnetic field distribution around the points under measurement, and a giant magneto-resistance (GMR) was used as a sensing element. Tikhonov regularization was applied to the inversion problem algorithm. Five different geometric defects machined in an aluminum plate were tested experimentally using the inversion algorithm. Finite element simulations are provided to validate the 2D eddy current density images obtained by the regularized inversion process. Highlights: Eddy current plane uniform field probe with GMR sensor. Inverse problem with Tikhonov regularization to get the eddy current fluxes. Defect geometry analysis by eddy currents imagiology.